2018
DOI: 10.1016/j.dib.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Data on prevalence of additive colors in local food and beverage products, Tehran, Iran

Abstract: The quality check and determination of permitted and non-permitted additive colors in food products is very important for customer׳s right protection and health. This survey was undertaken to demonstrate the frequently use of additive colors and products targeted to color adulteration in Iranian foods and beverages. From the 1120 of the samples, 18.86% contained artificial colors, 11.89% contained natural colors and 69.25% of samples had no additive colors. Tartrazine (E102) was the only non-permitted artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Comparing the thermal stability of phycocyanin, genipinderived pigments and anthocyanins of blue pea flower (Table 2), phycocyanin was less stable at low-temperature long time pasteurisation conditions (at 63 • C for 30 min) but Chaiklahan et al (2012) reported that the colour loss of phycocyanin in high-temperature short-time pasteurisation (71 • C for 15 s) was negligible. The thermal stability of genipin-derived pigments was higher in the alkaline medium compared with acidic and neutral media, but most of the blue coloured food products consist of an acidic pH (Asadnejad et al, 2018). Contrastingly, blue pea flower anthocyanins showed stability in acidic pH under pasteurising conditions (63 • C for 30 min).…”
Section: Stability Of Anthocyanins From Blue Pea Flowermentioning
confidence: 95%
See 2 more Smart Citations
“…Comparing the thermal stability of phycocyanin, genipinderived pigments and anthocyanins of blue pea flower (Table 2), phycocyanin was less stable at low-temperature long time pasteurisation conditions (at 63 • C for 30 min) but Chaiklahan et al (2012) reported that the colour loss of phycocyanin in high-temperature short-time pasteurisation (71 • C for 15 s) was negligible. The thermal stability of genipin-derived pigments was higher in the alkaline medium compared with acidic and neutral media, but most of the blue coloured food products consist of an acidic pH (Asadnejad et al, 2018). Contrastingly, blue pea flower anthocyanins showed stability in acidic pH under pasteurising conditions (63 • C for 30 min).…”
Section: Stability Of Anthocyanins From Blue Pea Flowermentioning
confidence: 95%
“…Both phycocyanin and genipin-derived pigments were not stable in the acidic medium whereas the blue pea flower anthocyanins demonstrated high stability in acidic pH around pH 3 to 5. Products such as soft drinks, fruit drinks and jelly mainly contain artificial blue colourants belonging to this pH range (Asadnejad et al, 2018). This could be considered as a major advantage of using blue pea flower anthocyanins as a blue colourant over phycocyanin and genipin-derived pigments.…”
Section: Stability Of Anthocyanins From Blue Pea Flowermentioning
confidence: 99%
See 1 more Smart Citation